Study of the influence of immunosupressive therapy on the state of the skin microbiocenosis of patients with acantholytic pemphigus - Kutasevych, Yanina; Oliinyk, Iryna; Dzhoraeva, Svitlana; Mashtakova, Iryna; Abdalla, Aliya; Oliinyk, Olha (Annals of Mechnikov’s Institute, 2021)
Introduction. Acantholytic pemphigus belongs to the group of severe autoimmune diseases. The clinical manifestation is damage to the skin and mucous membranes with a violation of their barrier role. Therapy requires long-term use of immunosuppressive drugs that promote remission of dermatosis and cause the development of imbalance in the microbiocinosis of the skin and mucous membranes. Secondary infections are a side effect of immunosuppressive therapy. The most common cause of skin bacterial infection is Staphylococcus aureus in 40.8% of patients, and according to AJ Kanwar and S. Dhar, sepsis was the most common cause of death among patients with acantholytic pemphigus, and S. aureus was the leading pathogen in 4 deaths. Material & methods. Patients with acantholytic pemphigus, 33 people who received immunosuppressive therapy for two months and more than 10 years were divided into three groups depending on the prevalence of the pathological process. Group I patients (severe) - 30.3%; Group II (moderate) - 51.5%, patients of group III - 18.2% had mild dermatosis. The comparison group consisted of 15 healthy individuals of the appropriate age and sex. The diagnosis was diagnosed according to classical clinical criteria and confirmed by cytological and laboratory tests. Identification of bacteria extracted from the skin and mucous membranes of the oral cavity was performed using the methods of classical bacteriology based on the study of morphological, cultural and biochemical properties. Determination of the sensitivity of the removed microorganisms to antibacterial drugs of different chemical groups was performed using the disk-diffusion method, the interpretation of the results was performed in accordance with international protocols and regulations of the Ministry of Health of Ukraine. Results & discussion. According to the results of bacteriological studies, 26 laboratory strains of opportunistic pathogens were isolated from the lesions on the skin and mucous membranes of I group patients, and were classified into three genera: Staphylococcus spp., Streptococcus spp., Acinetobacter spp. The "skin" habitat was dominated by representatives of the genus Staphylococcus - 76.9%. The density of colonization was 105 - 108 CFU / cm2. Examination of the material from the lesions on the mucous membranes, in the vast majority of patients found Staphylococcus spp. independently and in associations with microorganisms of the genus Streptococcus ,. The level of microbial contamination reached 106 - 108 CFU / ml. The intact areas were dominated by S. aureus, S. haemolyticus, S. epidermidis with a slightly lower percentage of microorganisms removed than in the lesions, and sometimes formed associations with Micrococcus spp. and non-pathogenic Corynebacterium spp. When analyzing the data to determine the levels of resistance of clinical strains of staphylococc removed from the lesions, it was found that the susceptibility of the removed pathogens was the highest to the drugs fusidic acid, oxazolidinones and mupirocin. In patients of II group during bacteriological examination of clinical material obtained from lesions on the skin and mucous membranes - isolated 36 laboratory strains of opportunistic pathogens, which were classified into three genera: Staphylococcus spp., Streptococcus spp., Klebsiella spp. and Proteus spp. Biotope "skin" - dominated by representatives of the genus Staphylococcus - 85.0% with a decrease in the proportion of staphylococci with a pronounced pathogenic potential - S. aureus (from 28.5% to 15.0%). The density of colonization was at the level of 105 - 106 CFU / cm2. The biotope "mucous" is represented by the association of coagulase-negative staphylococcus with Klebsiella and Proteus with a level of microbial contamination of 106 - 107 CFU / ml. The composition of the intact areas of the skin was similar to the affected areas. The microbial composition of the examined biotopes "skin", "mucous" patients of III group was almost similar to I and II groups, and intact areas of skin of patients almost did not differ in terms of dominant species of staphylococci from the affected areas. The degree of contamination of these cells on the skin was equal to 104 - 106 CFU / cm2. The microbial composition of the skin of the control group was characterized by the presence of mainly staphylococci, but with a significant species difference. Conclusion. According to the results of the study it was found that the microbiocenosis of the affected areas of skin and mucous membranes in patients with acantholytic pemphigus undergoes quantitative and qualitative changes in the species composition of microorganisms and correlates with the severity of dermatosis and duration of immunosuppressive therapy. Fusidic acid, oxazolidinones and mupirocin can be recommended for empirical therapy of microbial complications in this group of patients based on the determination of levels of resistance of clinical strains of staphylococci removed from the lesions. Due to the impossibility of using topical antimicrobial agents in the form of ointment forms in patients with AP, the use of aqueous aniline dyes and antibacterial drugs of systemic action remains relevant, taking into account the level of resistance of clinical strains of microorganisms (except penicillin and cephalosporin antibiotics). DOI: 10.5281/zenodo.5499649